ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SMA DENGAN TERHADAP MATERI SPLKDV - Siti Zakiyah; Luvy Sylviana Zanthy (Journal on Education, 2019)
The onjectives of this research are to know and analise mathematics problem solving student ability on Senior High School in Kabupaten Bandung Barat toward SPLKDV materials. The methode of this research are descriptive qualitative. This reserch conducted on 22nd November 2018 in the one of Senior High School in Kabupaten Bandung Barat with the sampel 27 students. Mathematic problem solving ability on Senior High School in Kabupaten Bandung Barat tough SPLKDV materials is 50,92% or middle category.